Communism - Legitimacy - Nationalism : Nationalist Legitimization of the Communist Regime in Poland - Zaremba, Marcin (2019)
This book is devoted to the issue of nationalism in the latest Polish history and presents the subject on the basis of an enormous amount of source files left by the Polish United Workers Party. The work is a substantial input into the knowledge on People's Poland which shows with precision how the Polish communists used nationalistic arguments to legitimize and validate the system of power introduced by them. The author researches the fascinating source material with the help of a new and innovative concept.